2013
DOI: 10.1002/chem.201301201
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium‐Containing Phosphinesulfonate Chelate for the Hydrogenation of Aryl Ketones

Abstract: Various ruthenium(II) complexes that contain phosphinesulfonate chelate have been synthesized. Arene-free complexes were found to be efficient in the base-free hydrogenation of various aryl ketones, whereas the arene-containing precatalysts required the presence of an amine as an additive. The seminal asymmetric hydrogenation reaction by using the new Sulfo-Binepine ligand was also investigated for the possible intervention of a dihydride species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 110 publications
(60 reference statements)
1
23
0
Order By: Relevance
“…In light of the potential reversible protonation and hemilability of the chelates in the resulting ruthenium complexes and the crucial influence of solvent, appropriate for the heterolytic cleavage of hydrogen, we next examined their reactivity towards acetophenone hydrogenation 6f,10d,29. The reactions were carried out at 50 °C in methanol under 50 bar of molecular hydrogen with a catalyst/substrate ratio of 1:100 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In light of the potential reversible protonation and hemilability of the chelates in the resulting ruthenium complexes and the crucial influence of solvent, appropriate for the heterolytic cleavage of hydrogen, we next examined their reactivity towards acetophenone hydrogenation 6f,10d,29. The reactions were carried out at 50 °C in methanol under 50 bar of molecular hydrogen with a catalyst/substrate ratio of 1:100 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…80 This property has been recently confirmed with the use of more rigid phosphinosulfonates. 30 It was shown that the treatment of deprotonated 2a-H with various ruthenium(II) precursors led to the corresponding ruthenium(II/IV) metallacycles.…”
Section: Ruthenium Complexesmentioning
confidence: 99%
“…30 Application in enantioselective hydrogenation with various ketones using [RuCl(p-cymene)(4h)] as chiral ligand afforded up to 92% ee. Bruneau et al demonstrated that the arene-free metal complex [RuCl(2a)(CH 3 CN) 3 ] was an efficient catalyst in the base free hydrogenation of aromatic ketones whereas the corresponding arene-containing precatalyst [RuCl(p-cymene) (2a)] required the presence of amines as the organic base inducing hydrogenation (Scheme 3.40).…”
Section: Ruthenium-catalyzed Hydrogenation Of Ketonesmentioning
confidence: 99%
See 1 more Smart Citation
“…The work on the spectroscopic properties and biological activities of cyclometalated P,O‐chelating Ir (III) complexes is rarely ever done. It should be noted that phosphine‐sulfonate ligands are currently attracting a lot of interest for their easily tunable structures and have been applied in catalysis . These developments encouraged us to prepare novel cyclometalated Ir (III) complexes bearing anionic phosphine‐sulfonate ligands and explore their biological activities.…”
Section: Introductionmentioning
confidence: 99%